The adoption of complex problem-solving practices and its impact in companies' ability to address strategic challenges - Loureiro, J.; Pereira, L. F. (IEEE Engineering Management Review, 2024)
Today's world is characterized by a fast-paced, constantly evolving environment, presenting companies and business managers with more complex, uncertain, and urgent challenges than ever before. To remain relevant, companies need to be alert, permanently identifying and addressing potential threats and opportunities. Continuous transformation plays a determinant role for companies that thrive and are successful. However, more than just the definition of solutions or decision-making processes, it is of the utmost importance to understand how companies identify, analyze, prioritize, and overcome these challenges. Due to its nature, strategic problems often entail a much higher risk than recurrent or at least known problems, thus becoming critical to analyze how business managers approach such problems. For that matter, building on the prior research of complex problem solving, this article followed a qualitative approach, carrying out semistructured interviews with open-ended questions to capture the real-life experiences of top managers within the challenging, dynamic, and fast environmental context of the corporate world. This enabled a comprehensive collection of relevant information and its consequent analysis through data mining techniques, thereby allowing to identify the type of approaches adopted to address strategic problems and the factors that have a greater influence on the application of such approaches.